Analysis of supply chain performance metrics for Indian mining & earthmoving equipment manufacturing companies using hybrid MCDM model. (October 2020) - Chand, Pushpendu; Thakkar, Jitesh J.; Ghosh, Kunal Kanti
Abstract: Companies with a high-performing supply chain (SC) often exhibit superior business performance. Therefore, companies are increasingly aligning their supply chain with business goals due to their impact on the firm's performance. Researchers acknowledge the importance of managing supply chain performance (SCP) in achieving greater customer experience and retention, increased cost-competitiveness, gaining market share with faster product innovation. Hence measuring and managing SCP is critical for a firm's business success. Though existing literature has explored key performance indicators (KPI) in measuring SCP but has rarely studied the interactions among the key SCP metrics and subsequent impact of overall SCP. To address the gap, present research work aimed to identify key metrics, rank them, investigate mutual relationship and propose integrated SCP metrics. Understanding the interrelationship among SCP metrics will enable supply chain practitioners in well-aligned decision making. To achieve this, a hybrid exploratory three-phased multi-criteria decision making (MCDM) model is adopted. The qualitative Delphi technique is initially applied to identify the critical SCP metrics, followed by Best-Worst Method (BWM) to rank SCP metrics, completed by decision making trial and evaluation laboratory (DEMATEL) method to establish the mutual relationship among the SCP metrics. The research finding, based on the study conducted for mining and earth-moving machinery manufacturing industry, suggests that sub-metrics such as flexibility in meeting customer needs, customer perceived value, operating cost of SC, employee productivity, range of products and services, are significantly contributing to the overall SCP. This study has proposed SCP metric selection model highlighting cross-functional and inter-organizational importance in performance management. Highlights: Supply chain performance metrics for Indian mining & earthmoving equipment manufacturing companies. Effect of interaction among metrics studied for superior supply chain performance (SCP). Three phased sequential research methodology DELPHI-Best-Worst Method-DEMATEL applied. Interrelationship among metrics will enable in well-aligned strategic decision making. Research highlighted cross-functional and inter-organizational importance in performance management.